2014
DOI: 10.1016/s1995-7645(14)60094-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spinal cord extracts after spinal cord injury on proliferation of rat embryonic neural stem cells and Notch signal pathway in vitro

Abstract: SCE could promote the proliferation of NSCs. It is demonstrated that the microenvironment of SCI may promote the proliferation of NSCs. Besides, SCE could increase the expression of Notch1 and Hes1 mRNA of NSC. It can be concluded that the Notch signaling pathway activation is one of the mechanisms that locally injured microenvironment contributes to the proliferation of ENSC after SCIs. This process may be performed by up-regulating the expressions of Notch1 and Hes1 gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…The Notch signal pathway renders the differentiation of spinal cord-derived stem cells into nerve cells, and inhibits that of neural stem cells into neurogliocytes, which contributes to the therapy for SCI (22). Notch signaling serves an important role in the development of the central nervous system, and Notch is essential for the directional differentiation and maintenance of the neural precursor cells (23). In a recent study, it was found that Notch and its relevant proteins were persistently expressed in the brain hippocampal area of adult mammals (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Notch signal pathway renders the differentiation of spinal cord-derived stem cells into nerve cells, and inhibits that of neural stem cells into neurogliocytes, which contributes to the therapy for SCI (22). Notch signaling serves an important role in the development of the central nervous system, and Notch is essential for the directional differentiation and maintenance of the neural precursor cells (23). In a recent study, it was found that Notch and its relevant proteins were persistently expressed in the brain hippocampal area of adult mammals (24).…”
Section: Discussionmentioning
confidence: 99%
“…It has been identified that manual intervention may promote the regeneration of nerve cells, and that moderate trauma can promote the proliferation and differentiation of the neural precursor cells that are in the stationary phase into nerve cells in the hippocampus of the mouse brain (33). In adult mice, the cells that are in the stationary phase (such as somatic stem cells) still have the ability to restart proliferation following years of cell cycle arrest; however, this requires changes in the expression quantity of the Hes1 protein, suggesting that Hes1 protein serves an important role in the development of the somatic cells, particularly the somatic stem cells (23). In addition, microglia activation, astrocyte proliferation and glial scar formation subsequent to SCI are the major factors that hinder the effective regeneration and growth of the injured axons (34).…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of Pax6 positively promote NSC self-renewal and neurogenesis ( Osumi et al, 2008 ; Sansom et al, 2009 ; Curto et al, 2014 ; Gan et al, 2014 ). The Notch1 signaling pathway has also been demonstrated to control NSC fate ( Kiparissides et al, 2011 ; Zhou et al, 2014 ; Stergiopoulos and Politis, 2016 ). The heatmap results indicated that the expression of several key stemness-related genes was upregulated in the Space group.…”
Section: Resultsmentioning
confidence: 99%
“…The NSCs in the dentate gyrus (DG) differentiated into neurons largely, which improved the spatial learning and memory ability of the mice and further restored the neurological function [ 114 ] (seen in Figure 2 ). The extracts from the injured spinal cord upregulated Notch1 mRNA, and the expression of Hes1 subsequently activated the Notch signaling pathway to promote NSC proliferation [ 115 ] (seen in Figure 2 ). Nevertheless, silencing the expression of Notch1 inhibited the division of NSCs and prevented NSCs from entering the cell cycle and maintaining self-renewal.…”
Section: Cell Signaling Pathwaysmentioning
confidence: 99%